Preliminary monitoring of glyphosate and its main metabolite in surface waters of the Santa Lucía River basin and in drinking water (INNOTEC, 2024)
The Santa Lucía River basin (CRSL) is the main source of drinking water supply for the population of Uruguay, and there is a significant use of the herbicide glyphosate (GLY)within it. The aim of this study was to carry out a  preliminary monitoring of GLY and its metabolite aminomethylphosphonic acid (AMPA) in surface waters (AS) of the (CRLS) as well as at raw water (AB) and in the drinking water (AP) of the Aguas Corrientes potablewater treatment plant (PPAC). GLY and AMPA were analyzed in 121 samples taken from August to December of 2020, 33 of which were AB from the PPAC, 33 were AP, and 55 were AS from the CRSL. It was found that in AB and AP the results for GLY and AMPA could not be quantified, which complies with national recommendations and regulations respectively. GLY and AMPA were detected and quantified in AS in the Canelón Chico creek sub-basin, with values below 1 μg/L. Even though these values comply withnational recommendations for natural waters, they exceed European Union regulations.Furthermore, this finding indicates that the Canelón Chico creek sub-basin is one of the worst quality tributaries of the CRSL.
Keywords: herbicides; water treatment process; diffuse pollution